Responding to the urban transformation challenges in Turkey: a participatory design model for Istanbul. Issue 1 (2nd January 2021) - Gün, Ahmet; Pak, Burak; Demir, Yüksel
ABSTRACT: Turkey is vulnerable to disasters such as earthquakes, flood, and landslides. Millions of housing units are planned to be demolished and rebuilt in the next 15 years within the scope of urban transformation. The existing legal framework and implementations are hardly participatory and thus cause conflicts. The aims of this study are: 1) to address the weaknesses and strengths of urban transformation practices in Turkey critically with a focus on Istanbul, and 2) to develop a new participatory design model for urban transformation processes by making use of contextualised ICT-based participation tools and techniques. This paper critically maps and discusses urban transformation processes in Istanbul by tracing how these practices take place on the ground and considering the different perspectives of stakeholder groups. We present an applicable model that consists of a system of participatory actions, interaction environments such as an expert collaboration platform developed specifically for Istanbul's urban transformation process.